Reescrituras contemporáneas de la esclavitud en las islas Canarias: los fantasmas memoriales en la novela histórica Epistolario de un nativo (2019) de Pedro Óscar Martínez Quintana - Claire Laguian (Cahiers de Civilisation Espagnole Contemporaine)
Not many publications exist about the history of colonization and slavery in the Canary Islands, and then a significant epistemic and memorial void remains in the contemporary Canarian imagination due to the total destruction of the native cultures and languages after the crimes of colonization and acculturation. There is no access to historical sources that would give voice to the native Canarian peoples, and due to these ghosts of the past and to the current search for a Guanche identity, literature faces this challenge of taking hold of the stories of slavery. The historical novel Epistolario de un nativo (2019) by Pedro Óscar Martínez Quintana is one of the examples of what a contemporary rewriting of the spectral colonial past can mean with its historical work, its counter-discourse in front of the official story of the Spanish State, its mythification and its contradictions, without forgetting its fictional stratagems and its positioning from a present that draws inspiration from the political struggles of the minorities.